Intradural Extramedullary Ewing Sarcoma in an Adolescent Female - Kunwald M; Straszek CL; Bjarkam CR; Ettrup MS; Skajaa T; Thomsen JL; Thusgaard M; Steiness MZ (Dove Medical Press, 2022)
Mikkel Kunwald,1 Christian Lund Straszek,2- 4 Carsten Reidies Bjarkam,1 Marianne Schmidt Ettrup,5 Torjus Skajaa,6 Janus Laust Thomsen,2 Mikkel Thusgaard,7 Morten Zebitz Steiness1 1Department of Neurosurgery, Aalborg University Hospital, Aalborg, Denmark; 2Center for General Practice, Aalborg University, Aalborg, Denmark; 3Department of Health Science and Technology, Aalborg University, Aalborg, Denmark; 4Department of Physiotherapy, University College of Northern Denmark, Aalborg, Denmark; 5Department of Pathology, Aalborg University Hospital, Aalborg, Denmark; 6The Department of Paediatrics and Adolescent Medicine, Aarhus University Hospital, Aarhus, Denmark; 7Family practice, Laegehuset i Hals, Hals, DenmarkCorrespondence: Mikkel Kunwald, Department of Neurosurgery, Aalborg University Hospital, Hobrovej 18-22, Aalborg, 9000, Denmark, Tel +45 97662400, Email m.kunwald@rn.dkAbstract: A 15-year-old female experiencing lumbar pain without prior trauma. Despite being prescribed strong analgesics by her family physician, the symptoms intensified, and she was referred to diagnostic imaging. Magnetic resonance imaging revealed an intradural extramedullary tumor in the spinal canal, located behind the L3 corpora. The patient underwent neurosurgery with a complete resection of the tumor. The histopathologic examination revealed Ewing sarcoma by identifying EWSR1 gene in the extracted tissue. The patient was subsequently referred for extensive specialized oncological treatment including photon irradiation therapy and chemotherapy. Thirty-six months on from the initial diagnosis, the patient is doing well and suffers no sequelae apart from hypogonadism.Keywords: intradural, extramedullary, Ewing sarcoma, tumor, spine, adolescent